Free‐breathing 3D late gadolinium enhancement imaging of the left ventricle using a stack of spirals at 3T. Issue 4 (3rd May 2014) - Pierce, Iain T.; Keegan, Jennifer; Drivas, Peter; Gatehouse, Peter D.; Firmin, David N.
<x xml:space="preserve">Abstract</x> Purpose To develop navigator‐gated free‐breathing 3D spiral late gadolinium enhancement (LGE) imaging of the left ventricle at 3T and compare it with conventional breath‐hold 2D Cartesian imaging. Materials and Methods Equivalent slices from 3D spiral and multislice 2D Cartesian acquisitions were compared in 15 subjects in terms of image quality (1, nondiagnostic to 5, excellent), sharpness (1–3), and presence of artifacts (0–2). Blood signal‐to‐noise ratio (SNR), blood/myocardium contrast‐to‐noise ratio (CNR), and quantitative sharpness were also compared. Results All 3D spiral scans were completed faster than an equivalent 2D Cartesian short‐axis stack (85 vs. 230 sec, P < 0.001). Image quality was significantly higher for 2D Cartesian images than 3D spiral images (3.7 ± 0.87 vs. 3.4 ± 1.05, P = 0.03) but not for mid or apical slices specifically. There were no significant differences in qualitative and quantitative sharpness (95% confidence interval [CI]: 1.91 ± 0.67 vs. 1.93 ± 0.69, P = 0.83 and 95% CI: 0.41 ± 0.07 vs. 0.40 ± 0.09, P = 0.25, respectively), artifact scores (95% CI: 0.16 ± 0.37 vs. 0.40 ± 0.58, P = 0.16), SNR (95% CI: 121.5 ± 55.3 vs. 136.4 ± 77.9, P = 0.13), and CNR (95% CI: 101.6 ± 48.4 vs. 102.7 ± 61.8, P = 0.98). Similar enhancement ratios (0.65 vs. 0.62) and volumes (13.8 vs. 14.1cm3) were measured from scar regions of three patients. Conclusio Navigator‐gated 3D spiral LGE imaging can be performed in significantly and substantially shorter acquisition durations, although with some reduced image quality, than multiple breath‐hold 2D Cartesian imaging while providing higher resolution and contiguous coverage. J. Magn. Reson. Imaging 2015;41:1030–1037. © 2014 Wiley Periodicals, Inc.